Break Event Point Analysis at Jempol Bakery - Massa, Dhella Pramestya; Fitriani, Tuti (ProBisnis : Jurnal Manajemen, 2024)
The purpose of this study was to determine how many sales in units and rupiah and how much tolerance for sales decline at Bakery Jempol. The data collection technique used in this research is interview. The data analysis instrument used in this research is using the break event point calculation method and margin of safety. The results of the Bakery Jempol business research will reach knowing how many sales in units and rupiah must be achieved in order to break even, it is necessary to calculate the break even point. From the results of the calculations that have been carried out, the Bakery Jempol business will break even if as many as 109,269 units or Rp 546,344,895, jempol bread is sold. burger bread will break even if as many as 51,218 units or Rp 128,044,701. bandung toast will break even if as many as 8,863 units or Rp 62,050,579. fresh bread will break even if there are 2,787 units or Rp 41,801,744. comb bread will break even if there are 17,548 units or Rp 70,193,704. mattress bread will break even if there are 2,186 units or Rp 34,754,897 and for hotdog bread will break even if there are 17,535 units or Rp 70,144,558. Bakery Jempol business can determine the tolerance for a decrease in sales of bakery products must be above sales per break-even point.